Are Olfactory Cues Involved in Nest Recognition in Two Social Species of Estrildid Finches? - Krause, E. Tobias (Public Library of Science, 2012)
Reliably recognizing their own nest provides parents with a necessary skill to invest time and resources efficiently in raising their offspring and thereby maximising their own reproductive success. Studies investigating nest recognition in adult birds have focused mainly on visual cues of the nest or the nest site and acoustic cues of the nestlings. To determine whether adult songbirds also use olfaction for nest recognition, we investigated the use of olfactory nest cues for two estrildid finch species, zebra finches (Taeniopygia guttata) and Bengalese finches (Lonchura striata var. domestica) during the nestling and fledgling phase of their offspring. We found similar behavioural responses to nest odours in both songbird species. Females preferred the odour of their own nest over a control and avoided the foreign conspecific nest scent over a control during the nestling phase of their offspring, but when given the own odour and the foreign conspecific odour simultaneously we did not find a preference for the own nest odour. Males of both species did not show any preferences at all. The behavioural reaction to any nest odour decreased after fledging of the offspring. Our results show that only females show a behavioural response to olfactory nest cues, indicating that the use of olfactory cues for nest recognition seems to be sex-specific and dependent on the developmental stage of the offspring. Although estrildid finches are known to use visual and acoustic cues for nest recognition, the similar behavioural pattern of both species indicates that at least females gain additional information by olfactory nest cues during the nestling phase of their offspring. Thus olfactory cues might be important in general, even in situations in which visual and acoustic cues are known to be sufficient.